On the altitude profile of lower ionospheric D-region response time delay during solar flares - Chakraborty, Sayak; Paul, Rakhi; Basak, Tamal (Frontiers in Environmental Science, 2022)
The D-region ionosphere is sluggish in nature while responding to the incoming solar radiation. We study the altitude ($h$) profile of mid-latitude D-region response time delay ($Δ t$) during three chosen solar flares, namely, C5.2, M5.2 and X2.2 classes. We solve `electron continuity equation' numerically at each and every $h$ to obtain $Δ t$-$h$ profile. We investigate the (i) latitudinal variation (over both northern and southern hemispheres) & (ii) seasonal variation (throughout the year) of $Δ t$-$h$ profiles of each of these solar flares separately. We go over noteworthy variations of $Δ t$-$h$ profile for both (i) & (ii) with reasonably different results over different hemispheres. Also, we study some contrasting behaviours of $Δ t$-$h$ profile of X2.2 class for both (i) & (ii) in comparison to C5.2 or M5.2 classes. We conclude the outcome with possible explanations.